Supplementation of Lauric Acid, Probiotic and their Combination on Performance and Immune Response of Commercial Broiler Chicken - Pappula, Radhika (Indian Journal of Animal Nutrition, 2021)
The objective of the present study was to determine the synergistic effect of lauric acid and probiotic on the performance of broiler chicken. A total of 250-day-old male broiler chicks were randomly distributed into five dietary treatment groups each having ten replicates with five chicks in each and were raised for a period of 42 days. Diets contained T1 - control diet, T2 - 0.05% antibiotic (AB), T3 - 0.05% lauric acid (LA), T4- 0.1% probiotic in the form of Bacillus subtilis PB6 (BS), and T5-0.05% organic acid +0.1% probiotic. The results revealed significantly (P<0.05) higher body weight gain, feed consumption and better feed conversion in LA+BS combination group followed by LA and BS alone compared to antibiotic (AB) and control diet at 42 d. The percent breast yield and thymus weights were increased (P<0.05) in LA and BS as compared to control diets. Humoral immune response (NDV titers) was higher (P<0.05) in LA+BS group followed by BS compared to control and AB. Further, no significant ((P>0.05) effect was observed on cutaneous basophilic hypersensitivity response among different treatments. Therefore, it can be concluded that supplementation of lauric acid (0.05%) + probiotic (0.1%) combination could be safely included as an alternative to antibiotic growth promoter in broilers.